Impact of Size, Leverage and Growth on Company Value - Empirical Study on Saudi Food Production Companies- - حاتم اياد; عفراء علي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to determine the effect of size, financial leverage and growth on the company’s value which measured by dividing Market Price Per Share by the Book Value Per Share. To achieve that goal; secondary data of 12 agriculture companies was collected from the annual financial reports and trading bulletins available of Saudi Exchange –Tadawul during the period from 2012 till 2021, with a total of 120 views. The data was organized and the values of the variables were calculated using Microsoft Excel 2010 and analyzed using the Eviews10 program. The study used Panel data, and the Auto Regressive Distributed Lag Model was used to analyze this data, because this model can be applied when the stability of the variables is a mixture between the level and the first difference. The Pooled Mean Groups (PMG) model was used. The results of hypothesis testing before adjusting profitability showed that the value of COINTEQ01error correction coefficient is (-0.60), and with control (-0.35), which is significant and indicates the existence of: cointegration relationship between the variables of the study. The results of hypothesis testing before adjusting profitability showed that: there is a significant negative effect of the company’s size on the value of the company in the short and long term; there is inverse, but not significant effect of financial leverage on the company’s value in the short term, while it was direct and significant in the long term; there is inverse, but not significant effect of growth in the company’s value in the short term, while it was positive and significant in the long term. Whereas; The results of hypothesis testing during profitability control showed that there is an inverse, non-significant effect of the size of the company on the value of the company in the short term, and the significant inverse effect in the long term. An inverse but non-significant effect of financial leverage on the company’s value in the short term, while it was positive and significant in the long term. A positive but not significant effect of the growth in the company’s value in the short term, while it was inverse and significant in the long term.